Holy Spirit Manifestations: a discussion about the gifts - Schanoski, Carolinne Louise Stefan Banderó; Westphal, Euler Renato (Vox Scripturae - Revista Teológica Internacional, 2016)
This paper addresses questions about the Holy Spirit, who he is, as was and is understood by the church and what their works are. After this explanation, the approach will specifically address the issue of the gifts of the Spirit. A brief explanation of the various gifts, their manifestation in the body of Christ and the church’s mission in the exercise of these different gifts.
Keywords: Holy Spirit; Gifts of the Holy Spirit; Mission